A local stress-strain approach for fatigue damage prediction of subsea wellhead system based on semi-decoupled model. (September 2020) - Li, Jiayi; Chang, Yuanjiang; Xiu, Zixiang; Liu, Haolin; Xue, Anti; Chen, Guoming; Xu, Liangbin; Sheng, Leixiang
Abstract: Subjected to complicated and cyclical dynamic loads caused by waves, currents and vessel motions and transferred by drilling risers, the subsea wellhead (SW) is prone to fatigue failure, which could lead to the loss of well integrity and even catastrophic accidents. This paper presented a novel semi-decoupled model based local stress-strain approach to predict the fatigue damage of SW. Using the proposed method, a local fine finite element model of SW was built to analyze local load-strain curves of fatigue hot-spots and the equivalent model of the SW. Further, the equivalent model was put into the global model to extract load-time curve by dynamic analysis. After the strain-time curve was determined by the calculated load-strain and load-time curves, the strain range could be calculated by the stabilized hysteresis curve and rainflow counting. Subsequently, the fatigue damage was calculated by the modified strain-life curve and Palmgren-Miner's rule. The results of a case study indicated that the fatigue damage of high pressure wellhead (HW) weld was higher than that of low pressure wellhead (LW) weld, as the LW has the larger outside diameter and wall thickness causing the larger bending stiffness. Compared with the conventional S-N method of fatigue analysis, the calculation results of the proposed semi-decoupled model based local stress-strain approach would be more efficient and reasonable, and the related conclusions could provide reference for life extension of SW in deepwater oil and gas development.